REGULASI DIRI, EFIKASI DIRI DAN PROKRASTINASI SANTRI PONDOK PESANTREN AL-IMAM ASHIM MAKASSAR DALAM MENGHAFAL ALQURAN - Sulaiman, Abdul Rajab; Saprin; Wahyuni Ismail (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research aims to determine the level of relationship between self-regulation and self-efficacy with academic procrastination in memorizing the Al-Qur'an for students at the Al-Imam Ashim Islamic Boarding School, Makassar. The type of research used is ex post facto with quantitative methods. With a sample size of 51. The instrument used was a questionnaire. Data analysis uses simple and multiple descriptive and inferential statistical techniques. The results showed self-regulation was 60.7 and was in the good class interval category. The average score for self-efficacy is 37.05 in the medium category. The average value for procrastination is 37.62 in the low category. The results of simple and multiple regression analysis indicate that there is a relationship between self-regulation and self-efficacy, with the calculated r-value being greater than the r-table, namely 0.358 and 0.279 with a significance of 0.05, then there is an opposite relationship between self-efficacy. regulations and delays. The calculated r-hypothesis test value is smaller than the r-table, namely -0.470 and 0.279 with a significance of 0.003 <0.05. Then the relationship between self-efficacy and procrastination is the opposite. The hypothesis test value rcount = -0.665 rtable = 0.279 with a significance of 0.001 <0.05 is accepted. There is a relationship between self-regulation, self-efficacy together with procrastination, with a value of 0.529 with a significance of 0.000 <0.05. This research implies that students' procrastination in memorizing the Al-Quran at Al-Imam Ashim Islamic Boarding School Makassar can be emphasized by increasing self-regulation based on the theory studied in this research.